Badan Pengkajian Ideologi Pancasila dalam Perspektif Hukum Tata Negara - Gaol, Dora Nina Lumban (Jurnal Konstitusi & Demokrasi, 2021)
The development of state institutions experiences dynamics in accordance with the need to exercise state power. One of the needs that is considered important by decision makers is the importance of fostering the ideology of Pancasila to all state administrators which ended in the creation of newstate institutions called Pancasila Ideology Guidance Agency (BPIP). The existence of this institution became something debatable s from the most basic: the urgency of fostering ideology in Indonesia. Pros and cons were also born related to the position, duties, and functions as written in Presidential Regulation Number 7 Year 2018 about the Pancasila Ideology Guidance Agency. Differences views regarding its relationship with other state institutions also became an issue in the study of Constitutional Law. With normative juridical research, this study aims to explain the position and authority of the Pancasila Ideology Guidance Agency in the constitutional system in Indonesia. The author also examines the potential for overlapping with other state institutions regarding their duties and functions. As an enrichment the author brings an example of the views of the constitutions of several countries related to ideology.